The Effects of Leadership and Communication of the Village Head among the Community Participation in the Development of Walea Islands Sub-District, Tojo Una-Una Regency of Central Sulawesi - Darwan S. Usman; Arifin Tahir; Ismet Sulila (Jurnal Ilmu Manajemen dan Bisnis, 2022)
The objectives of this study are: 1) to determine how much influence partially the village head's leadership has on community participation in development in Walea Islands Sub-District, TojoUna-Una Regency; 2) to find out how much influence partially the village head's communication has on community participation in development in Walea Islands Sub-District, Tojo Una-Una Regency; 3) to determine how much influence simultaneously the leadership and communication of the village head on community participation in development in Walea Islands Sub-District, TojoUna-Una Regency. Quantitative descriptive research method approach with survey research type that explains the caesal relationship and conduct hypothesis testing with multiple regression analysis approach. The results show that: 1) there is a positive and significant influence between the leadership variable of the village head on community participation in development in the Walea Islands Sub-District, TojoUna-Una Regency. This means that the increased leadership of the village head, the community participation will also increase; 2) There is a positive and significant influence between the communication variables of the village head on community participation in development in Walea Islands Sub-District, TojoUna-Una Regency. This means that the better the communication of the village head, the better and increasing community participation; 3) There is a joint influence between the leadership and communication of the village head on community participation in development in Walea Islands Sub-District, TojoUna-Una Regency. This means that if leadership and communication are carried out properly by the village head. It can increase community participation in development.